2012
DOI: 10.1155/2012/830741
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Strains in Modeled Optohydrodynamically Stressed Healthy and Diseased Biological Cells

Abstract: Controlled external chemomechanical stimuli have been shown to influence cellular and tissue regeneration/degeneration, especially with regards to distinct disease sequelae or health maintenance. Recently, a unique three-dimensional stress state was mathematically derived to describe the experimental stresses applied to isolated living cells suspended in an optohydrodynamic trap (optical tweezers combined with microfluidics). These formulae were previously developed in two and three dimensions from the fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The recorded stress values are in a logical concordance with previous experimental and computational studies of cell biomechanics using fluid flow . Several recent cell biomechanical investigations applied flow‐induced shear stresses in the physiologic range on adherent cells .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The recorded stress values are in a logical concordance with previous experimental and computational studies of cell biomechanics using fluid flow . Several recent cell biomechanical investigations applied flow‐induced shear stresses in the physiologic range on adherent cells .…”
Section: Discussionsupporting
confidence: 85%
“…It has been shown that cells would experience about 350 mPa normal stress due to the flow passing over it . Kohles et al, treating the mechanical properties of a single cell in a macroscopic approach as an isotropic homogenous continuum model , recorded a maximum value of 500 mPa effective stress along with 10% volumetric strain in normal healthy cells . A maximum value of 5‐μm cell deformation was also reported by Kohles et al in the assumed flow velocity of 2000 μm/s .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation